Automatización del método de evaluación simplificado de corrosión de la estructura de concreto armado - Aguilar-Brenes, Andrea (Instituto Tecnológico de Costa Rica, 2007)
The researches to increst the durability of reinforced concrete structure and to extend the structure development have find a big trouble because its structure has the inconvenience of being potentially susceptible to be damage by corrosion. The problem of the concrete structures degradation is serious and of major economic implications. The difficulty to asses and interpret the corrosion severity show the importance to give a hand to the engineer, students and all the employers related in this field. In the next chapters there is a tool who make easier the inspection scheduling and the ability to asses the corrosion severity and solutions may use. The reader should be able to use a program manual and will find the knowledge of the corrosion fundamentals detailed.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Lenguaje computacional; Inspección; Vida útil; Corrosión; Métodos de prevención